Influence of climacteric hormonal changes on buccal tissues - Oliveira, Natalia Pereira de; Gomez, Nicolás Antonio Douglas (ABCS Health Sciences, 2019)
During the climacteric period, when female gonads cease their function, estrogen deficiency, especially estradiol, causes important changes in the oral cavity, interfering in inflammatory mechanisms, salivary secretion, collagen metabolism, among others. Through a literature review, this study aimed to see the influence of the hormonal changes from the climacteric period in the oral tissues, providing the dentist surgeon with information regarding the consequences and care related to this phase of the woman's life. In this period, women become more susceptible to changes such as: osteopenia and osteoporosis of the jaws, hyposalivation, periodontal diseases, among others. Preventive treatment through removal of plaque, adequacy of the buccal environment and orientation before and during climacteric are the best means of minimizing oral problems arising from this phase of a woman's life.